Anterior Segment Optical Coherence Tomography of Patients With Late-Onset Tunnel Fungal Infections With Endophthalmitis After Cataract Surgery. Issue 8 (August 2016) - Kitahata, Mami; Suzuki, Takashi; Oka, Naoko; Toriyama, Koji; Ohashi, Yuichi
Abstract : Purpose: To report the use of anterior segment optical coherence tomography for characterization of late-onset tunnel fungal infections with endophthalmitis after cataract surgery. Methods: Case reports. Results: A 77-year-old female (case 1) and a 76-year-old male (case 2) who received cataract surgery 15 and 1 year before their initial visits, respectively, were treated with topical steroids based on a diagnosis of uveitis, because they showed growing white lesions on the upper iris and beneath the cataract scleral wound. Irrigation of the anterior chambers and removal of the white lesions were performed in each case, and microbiological tests were positive for fungi (case 1, a positive culture of Fusarium sp.; case 2, a filamentous fungus present in a direct smear) in the white lesions. Both cases were diagnosed as late-onset fungal endophthalmitis after cataract surgery and were treated with topical and systemic antifungal agents. However, the white lesions reappeared, and the inflammation in the anterior chambers worsened. Anterior segment optical coherence tomography showed the spread of the white lesions into the scleral incisions from cataract surgery. Deroofing of the tunnel and sclerocorneal patch grafts were performed in both cases to treat the fungal tunnel infections. After these treatments, inflammation of both corneas and anterior chambers subsided. Conclusions: Anterior segment optical coherence tomography can be used to identify late-onset fungal tunnel infections with endophthalmitis after cataract surgery.